So, i would use the add the two equation method, so add those to get:
2e=-4
e=-2
then plug in e to get d, so d+-2=1
d=3
plug into the other one to make sure
-3+-2=-5
so it would be (3,-2)
Answer:
Step-by-step explanation:
we would like to expand the following logarithmic expression:
remember the multiplication logarithmic indentity given by:
so our given expression should be
by exponent logarithmic property we acquire:
hence, our answer is A
The measure of G is 28 because it is an isosceles triangle
Answer:
Step-by-step explanation:
Given the expression